Peningkatan Kemampuan Usaha Mikro Kecil Dan Menengah Melalui Pelatihan Pencatatan Akuntansi - Purnama, Chamdan; Rahmah, Mirhamida; Fatmah, Dinda; Rahmah, Zakiyah Zulfa (Pakis Journal Institute, 2024)
Micro, small and medium enterprises (MSMEs) that are resilient in facing the economic crisis have the potential to become an important economic driving force by being able to absorb labor and significantly reduce the unemployment rate. However, MSMEs often face challenges in managing their financial aspects, especially in terms of proper and correct accounting records. To overcome this problem, training is an effective solution. Training on good and correct accounting records can help MSMEs entrepreneurs to increase their understanding in managing their business finances. The results of the implementation of this training activity show that MSME entrepreneurs initially did not understand the accounting recording process, but after going through the training, they were able to improve their abilities in this matter. Thus, training on accounting records can be an effective step in strengthening MSMEs and helping them face the various challenges they face in managing their businesses financially.